Analysis of Inpatient Linen Management in Hospital Isolation Room in Indonesia: A Review - Yulis Muktafi'ah; Antono Suryoputro; Septo Pawelas Arso (Universitas Aisyah Pringsewu, 2021)
Linen handling activities are a very important handling activity carried out in hospitals. The thing that can minimize the risk of distribution of linen is to carry out proper handling according to standards. If the handling is carried out properly, the risk of spreading microorganisms to activities, staff, and the environment can be carried out and minimized. The purpose of writing this article is to find out the analysis of inpatient linen management in isolation rooms in various hospitals in Indonesia. The method used in writing this article is a qualitative method with the strategy used is a literature study on the topic of analysis of linen management in hospital isolation rooms in Indonesia. The results of the literature from various sources found that hospitals in Indonesia had set standards for linen management to prevent transmission. However, linen management in various hospitals in Indonesia, in general, has not been able to run optimally and has not met the applicable standards. This can be seen from the various stages of handling linen that does not meet the standards starting from the stages of separation, reception, processing, washing, and storage. Abstrak: Kegiatan penanganan linen merupakan sebuah kegiatan penanganan yang sangat penting dilakukan di rumah sakit. Hal yang dapat meminimalisir risiko penularan dari linen yaitu dengan melaksanakan penanganan yang tepat sesuai dengan standar. Jika kegiatan penanganan dilakukan dengan tepat, maka risiko penularan mikroorganisme pada pasien, petugas serta lingkungan dapat dicegah dan diminimalisir. Tujuan penulisan artikel ini yaitu untuk mengetahui analisis pengelolaan linen rawat inap ruang isolasi di berbagai rumah sakit di Indonesia. Metode yang digunakan dalam penulisan artikel ini yaitu metode kualitatif dengan strategi yang digunakan adalah studi literatur dengan topic analisis pengelolaan linen rawat inap ruang isolasi rumah sakit di Indonesia. Hasil tinjauan pustaka dari berbagai sumber yang ditemukan menyatakan bahwa rumah sakit di Indonesia sudah menetapkan standar pengelolaan linen untuk mencegah risiko penularan. Namun, pengelolaan linen di berbagai rumah sakit di Indonesia secara garis besar belum dapat berjalan dengan maksimal dan belum memenuhi standar ketentuan yang berlaku. Hal ini dapat dilihat dari berbagai tahap kegiatan penanganan linen yang belum memenuhi standar mulai dari tahap pemisahan, penerimaan, pengangkutan, pencucian dan penyimpanan.